Capital Requirements with Non-Bank Finance - Dempsey, Kyle (Review of Economic Studies, 2026)
Abstract I quantitatively analyse the macroeconomic impacts of raising capital requirements in a model in which heterogeneous firms may choose either intermediated or direct finance. Heterogeneous banks compete with other banks and the bond market, fund loans with insured deposits and costly equity (subject to a minimum capital-to-asset ratio), and monitor borrowers. I find that tighter capital requirements reduce costly bank failures while having only small effects on key macroeconomic aggregates, and that raising capital requirements above current levels can be welfare-improving. Three main forces give rise to these results. First, even though banks cut loan supply for a given level of net worth under a tighter capital requirement, in equilibrium banks’ net worth rises to dampen this effect. Second, intense competition from the non-bank sector disciplines banks’ lending responses to tighter regulation. Third, substitution by corporate firms offsets much of the decline in debt financing associated with tighter bank loan supply. As a corollary, almost all of the modest costs associated with tighter capital requirements are concentrated within the bank-dependent non-corporate sector.